Black-white marital matching: Race, anthropometrics, and socioeconomics - Pierre-André Chiappori; Sonia Oreffice; Climent Quintana-Domeque (Institute for the Study of Labor (IZA), 2011)
We analyze the interaction of race with physical and socioeconomic characteristics in the U.S. marriage market, using the Panel Study of Income Dynamics from 1999 to 2009 for black, white, and inter-racial couples. We consider the anthropometric characteristics of both spouses, together with their wage and education, and estimate who inter-racially marries whom along these dimensions. Distinctive patterns arise by gender and race for inter-married individuals: the black women who inter-marry are the thinner and more educated in their group; instead, white women are the fatter and less educated; black or white men who inter-marry are poorer and thinner. While women in mixed couples find a spouse who is poorer but thinner than if they intra-married, black men match with a white woman who is more educated than if they intra-married, and a white man finds a thinner spouse in a black woman.
urn:nbn:de:101:1-201201104626
Keywords: D1; J1; 330; interracial couples; marriage market; BMI; wages; education; Ehe; Farbige Bevölkerung; Weiße; Körpergewicht; Einkommen; Schätzung; USA